Climate change and agricultural productivity: Economic implications for food security - Riza Murabildayeva; Laila Bimendiyeva; Saltanat Kondybayeva; Zhanna Yermekova (Наукові горизонти)
Since the late 20th century, there has been an increasing focus on the impact of climate change on various sectors, including agriculture. Consequently, it is crucial to assess how the negative effects of climate change can be mitigated to ensure food security. This study evaluated the relationship between agriculture, food security, and CO2 emissions. In particular, a correlation analysis was conducted between selected indicators for three countries: Kazakhstan, the United States of America, and Germany, as a representative of European Union countries. The study demonstrated that rising temperatures, changes in precipitation patterns, and the increased frequency of extreme weather events significantly disrupt agricultural productivity, posing substantial risks to global food security. These issues were compounded by the need to adapt agricultural methods and technologies to new climatic realities, which often require significant financial and human resources, particularly in developing countries with limited resources. Conclusions drawn from statistical data revealed mixed results: for Kazakhstan, the positive impact of agriculture on food security was confirmed, while CO2 emissions had an ambiguous effect on food security indicators. The findings of this study can be used to inform strategies for future development, both by enterprises and by the state as a whole